Pengaruh Literasi Keuangan, Religiusitas, dan Lingkungan Sosial terhadap Ketahanan Ekonomi Keluarga Pasca Pandemi Covid-19 di Kelurahan Margadana, Kota Tegal - Miftah Farid; Liana Fuadah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to analyze the influence of financial literacy, religiosity, and social environment on family economic resilience in the post-Covid-19 period in Margadana Village, Tegal City. The Covid-19 pandemic has significantly affected the socio-economic conditions of communities, particularly in terms of family welfare and financial management capabilities. This research employs a qualitative approach with a case study design, involving heads of households, community leaders, religious figures, and local government officials as key informants. Data were collected through in-depth interviews, field observations, and documentation, and analyzed using Miles and Huberman’s interactive model, including data reduction, display, and conclusion drawing. The results reveal that sound financial literacy enables families to manage their economic resources effectively, religiosity shapes ethical and disciplined financial behavior, and the social environment provides both moral and material support that strengthens family resilience. These three factors interact synergistically to build family economic resilience in the post-pandemic era. The findings highlight the importance of enhancing financial literacy grounded in religious and social values as a sustainable strategy to strengthen community-based family welfare.